Losses of human beings - Vanderstein, Noémi (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Losses are essential in every human being's life. My goal is to make an attempt to introduce the main aspects of loss. I think that losses occur by two modes: in our cultural surroundings and in our identity. Culture plays an important role in people's lives, culture that we are bom into. However, Otherness is a new field of investigating the individuals and of investigating the world at the same time. What is the end of losing culture? What is the end of losing Otherness? To reach the state of being a Subject is the unconscious desire of human beings' psyches. Every human being reaches a development in his thinking, and he becomes a Subject through his losses because these losses serve as profit at the same time.